Analisis Pendapatan dan Pola Pengeluaran Rumah Tangga Petani Kelapa Desa Manunggal Makmur Kecamatan Kuala Kabupaten Tanjung Jabung Timur - Ambarwati Wibowo; Syaparuddin; Erni Achmad (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the income of coconut farming, determine household expenditure patterns, evaluate the comparison between farmers' income and expenditures, and analyze the effects of land area, number of trees, crop yield, plant age, and coconut prices on farming household income in Manunggal Makmur Village, Kuala Jambi District, Tanjung Jabung Timur Regency. The research was conducted in May 2026 utilizing a survey method. The research sample consisted of 63 farmers selected through a purposive sampling method. The data comprised primary data gathered through interviews using questionnaires and secondary data obtained from relevant institutions. Data were analyzed using a descriptive quantitative approach through the calculation of production costs, income, and household expenditures, as well as statistical analysis to measure the effects of land area, number of trees, crop yield, plant age, and coconut prices.